COVID-19 Epidemic and Public Health Measures in China - Tingting Xu; Ruoyu Yang (Springer, 2020)
Objectives: The study aims to analyze the status quo of public health emergency measures taken in China in dealing with the spread of new coronavirus pneumonia (COVID-19), and to put forward policy suggestions for system construction and improvement. Methods: According to the official data released by the National Health Commission, the epidemic data of infected people from 0:00 on January 24, 2020 to 24:00 on February 23, 2020 were quantitatively analyzed through statistical analysis. We used EXCEL software to draw the overall epidemic trend chart and Statistical Product and Service Solutions (SPSS) to carry out descriptive statistical analysis of mortality and cure rate. We made qualitative analysis on the emergency measures implemented by national administrative departments and provincial governments to work on controlling and monitoring COVID-19 nationwide spread. Results: The number of patients diagnosed showed a linear increasing trend, with the slope increasing first and decreasing later. Suspected and new cases showed an inverted V pattern, with the peak occurring on February 8 and 12, respectively. There was a linear increase in the number of deaths and an exponential increase in the number of cures. Over the 31-day study period, the mortality rate fluctuated between 2.0% and 3.4%. The mean cure rate was 10.03%, the minimum value was 1.33%, and the maximum value was 32.05%. The quantitative and qualitative analysis shows that the public health emergency response system constructed in China plays a significant role in controlling the epidemic in a certain period of time. Discussion: The four-tier emergency management system and the joint prevention mechanism established in China have provided various resources to control the epidemic, but there are still weakness in dealing with the spread of COVID-19. It is suggested to improve and strengthen the emergency management system, public health service system, health legal system, citizen health education, and international exchange and cooperation.